Development of a High Protein Dairy Snack Based on German-Style Quark Cheese - Y. Ou; K. S. Babu; P. Thorakkattu; K. Getty; J. Amamcharla (Kansas Agricultural Experiment Station Research Reports, 2018)
Current consumer trends highlight the need for developing convenient and ready-to-eat snack foods that render health benefits when consumed. Rising popularity of protein-enriched foods and beverages have led to increasing awareness among consumers of health benefits related to a dairy-rich diet. The vast majority of people have adopted this lifestyle, spotting the protein’s importance in delivering vital nutrients for health and maintenance of the body, curbing hunger, sustaining a slow release of energy, and speeding the metabolism. Innovation is the key driver for the dairy snack market. The primary objective of this project was to develop an American-sourced predominantly dairy (>51%) snack which meets both the current snacking trends and REAL® Seal requirement. The research also focused on assessing the acceptance of a dairy snack (“Quick-Quark”) formulated with German-style quark cheese. An acceptance test with consumers using a 9-point hedonic and a “just-about-right” scale showed that flavor, mouthfeel, and texture attributes were within the liking rate of consumers. Furthermore, the higher protein content in the Quick-Quark gives this product an added value that may have a great influence on consumers’ preference.
Keywords: Quark cheese; snack; milk protein concentrate